Coated sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

By using a mixture of aluminum oxide and hydroxide and polyvinylidene fluoride on the positive electrode material of sodium ion battery for in-situ chemical coating, the problem of poor air stability of layered transition metal oxide materials is solved, and the performance and stability of the battery are significantly improved.

CN119812250APending Publication Date: 2025-04-11ZHEJIANG SUPER SODIUM NEW ENERGY MATERIALS CO LTD

Patent Information

Application Number
CN202411909635.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When layered transition metal oxides are used as the positive electrode material of sodium ion batteries, the air stability is poor and it is easy to absorb water molecules to form residual alkali substances on the surface, resulting in high impedance and material degradation, affecting battery performance.

Method used

A mixture of aluminum oxide and/or hydroxide, aluminum-containing salt and polyvinylidene fluoride is used as the coating to generate a uniform and stable coating layer through in-situ chemical reactions, reducing residual alkali, supplementing Na ions, forming strong bonds, and improving the stability of the outer layer structure.

Benefits of technology

It significantly improves the air stability, rate performance and cycle stability of the positive electrode material of sodium ion battery, reduces the residual alkali on the surface of the material, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812250A_ABST
    Figure CN119812250A_ABST
Patent Text Reader

Abstract

The invention discloses a coated sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery, the coated sodium ion battery positive electrode material comprises a base material and a coating layer coating the base material, the coating layer is generated by chemical reaction of the base material and a coating, the chemical formula of the base material is NanNiaFebMncXdO2, n is more than or equal to 0.8 and less than or equal to 2, a is more than or equal to 0.1 and less than or equal to 0.6, x is more than or equal to 0.8 and less than or equal to 1, and x is more than or equal to 1 and less than or equal to 2. A + b + c is greater than or equal to 0.7, d is less than or equal to 0.3, and X is selected from at least one of Ti, Mg, Zr, B, Al, Mo, Ca, Co, Li, Cu, Y, W, Sr, La, Nb and Si; the coating comprises a mixture of polyvinylidene fluoride and at least one of aluminum oxide and / or hydroxide and aluminum-containing salt. The coating layer on the surface of the base material is obtained through an in-situ chemical reaction instead of simple physical coating, the obtained coating layer has a good synergistic effect, residual alkali on the surface of the sodium ion battery positive electrode material can be reduced, and the air stability, rate capability, cycling stability and the like of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a coated sodium-ion battery cathode material and its preparation method, as well as a sodium-ion battery. Background Technology

[0002] In recent years, sodium-ion batteries, which possess similar physicochemical properties to lithium-ion batteries, have attracted widespread attention and research due to their abundant resources, environmental friendliness, and high energy density. Sodium-ion battery cathode materials mainly include layered transition metal oxides, polyanionic compounds, Prussian analogs, and tunnel oxides, among which layered transition metal oxides have seen rapid development due to their high energy density and ease of technology transfer. However, layered transition metal oxides exhibit poor air stability, readily absorbing water molecules to generate surface alkaline substances, leading to high impedance. During cycling, they undergo side reactions with the electrolyte, causing metal ion dissolution, material degradation, and ultimately affecting the performance of sodium-ion batteries.

[0003] Surface coating technology is one of the effective methods to address these problems. It involves coating the surface of electrode materials with materials to improve their electrochemical properties, such as air stability. Surface coating methods can generally be divided into wet coating and dry coating. Wet coating refers to the process of fully dissolving and dispersing the coating material in a dispersant, adding it to the matrix, and then stirring, evaporating, or filtration. This allows the additive to undergo a chemical reaction and precipitate on the matrix surface, forming a surface coating layer. The coating layer is then sintered to react and solidify. However, its preparation process is complex and the production cost is high.

[0004] Therefore, in actual production, dry coating is mostly used. Dry coating refers to physically mixing the coating material with the substrate. During the mixing process, friction and collision occur, causing the coating material to be uniformly dispersed on the substrate surface to form a coating layer. The coating is then reacted and cured by sintering. For example, invention patent application CN 115954447A discloses a hydrophobic polymer-coated modified sodium-ion battery cathode material, its preparation method, and a battery. The modified sodium-ion cathode material includes a sodium-ion cathode material and a coating material. The preparation method includes placing hydrophobic polymers and sodium-ion cathode materials in different mass ratios in a high-energy ball mill and ball milling at 500–1000 rpm for 1–48 hours at room temperature to 50°C to obtain the modified sodium-ion battery cathode material. However, because the coating is a simple physical mixing process, it involves factors such as mixing uniformity and ion diffusion, resulting in poor coating effect and low uniformity, failing to effectively improve the air stability and other properties of the sodium-ion battery cathode material. Summary of the Invention

[0005] To address the aforementioned problems, in a first aspect, the present invention provides a coated sodium-ion battery cathode material that exhibits good cycle stability and air stability.

[0006] The technical solution of the present invention to solve the above problems is as follows:

[0007] A coated sodium-ion battery cathode material includes a matrix material and a coating layer covering the matrix material. The coating layer is formed by a chemical reaction between the matrix material and the coating material. The chemical formula of the matrix material is Na. n Ni a Fe b Mn c X d O2, wherein 0.8≤n≤2, 0.1≤a≤0.6, a+b+c≥0.7, d≤0.3, and X is selected from at least one of Ti, Mg, Zr, B, Al, Mo, Ca, Co, Li, Cu, Y, W, Sr, La, Nb, and Si; the coating comprises: at least one of aluminum oxides and / or hydroxides, aluminum-containing salts, and polyvinylidene fluoride.

[0008] Preferably, the total mass of aluminum in the aluminum oxides and / or hydroxides and aluminum-containing salts is 1000 to 8000 ppm of the mass of the matrix material.

[0009] Preferably, the mass of the polyvinylidene fluoride is 1000 to 8000 ppm of the mass of the matrix material.

[0010] Preferably, the coating comprises a mixture of at least one of alumina and aluminum hydroxide with polyvinylidene fluoride.

[0011] Secondly, the present invention also provides a method for preparing the above-mentioned coated sodium-ion battery cathode material, comprising the following steps:

[0012] S1. Mix the sodium source, nickel source, iron source, manganese source and X source evenly to obtain a primary mixture;

[0013] S2. The primary mixture is placed in an air atmosphere furnace for solid-state sintering, crushed, and sieved to obtain the matrix material.

[0014] S3. Mix the matrix material and the coating material evenly to obtain a secondary mixture;

[0015] S4. The secondary mixture is placed in an air atmosphere furnace for sintering and then sieved to obtain a coated sodium-ion battery cathode material.

[0016] The matrix material has poor air stability, and the Na in it... + With H in the air + Ion exchange occurs, Na +After being removed, it reacts with H2O or CO2 in the air, forming residual alkalis such as NaOH or Na2CO3 on the material surface. In this invention, the polyvinylidene fluoride (PVDF) in the coating reacts in situ with the residual alkalis on the matrix material surface to remove fluoride, consuming OH groups while generating HF. - The generated HF continues to react with Al-containing substances (aluminum oxides and / or hydroxides, or at least one aluminum-containing salt) in the coating to form AlF3. Simultaneously, HF also reacts with residual alkali substances to form NaF and other substances. During subsequent high-temperature solid-state sintering, Na, Al, and F ions diffuse from the outside in at high temperatures, replenishing the missing Na ions and forming strong bonds such as Na-O-Al, Na-F, TM-F (TM being a transition metal element), and Al-F. This improves the stability of the outer layer structure and inhibits irreversible phase transformation and the dissolution of transition metals. The surface of the coated material contains various substances, such as the hydrophobic PVDF remaining from the reaction, which, together with the coating layer, prevents moisture and electrolyte from penetrating into the particle interior. The reaction also consumes residual alkali substances, all of which improve the air stability and cycling stability of the coated material. Furthermore, the generated AlF3 substance significantly promotes the maintenance and improvement of cycling performance and rate capability.

[0017] Preferably, in step S1, the sodium source is selected from at least one of sodium hydroxide and sodium-containing salts; the nickel source is selected from at least one of nickel oxide, hydroxide, and nickel-containing salts; the iron source is selected from at least one of iron oxide, hydroxide, and iron-containing salts; the manganese source is selected from at least one of manganese oxide, hydroxide, and manganese-containing salts; and the X source is selected from at least one of X oxide, hydroxide, and X-containing salts.

[0018] More preferably, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium nitrate, and sodium bicarbonate.

[0019] More preferably, the nickel source is selected from at least one of nickel oxide and nickel hydroxide.

[0020] Further preferably, the iron source is selected from at least one of ferric oxide and ferric oxide.

[0021] More preferably, the manganese source is selected from at least one of manganese oxide, manganese dioxide, and manganese tetroxide.

[0022] Preferably, in step S2, the sintering temperature is 900–1100°C, the heating rate during the sintering process is 2–10°C / min, and the sintering time is 8–12 h.

[0023] Preferably, in step S2, the mesh size of the sieve is 200 to 400 mesh.

[0024] Further preferably, in step S2, the mesh size of the sieve is 200, 300, or 400.

[0025] Preferably, in step S4, the sintering temperature is 250–650°C, the heating rate during the sintering process is 2–10°C / min, and the sintering time is 4–8h.

[0026] Preferably, in steps S2 and S4, the air is dry compressed air.

[0027] Preferably, in steps S2 and S4, crushing and sieving are carried out in a dehumidified environment.

[0028] The present invention has the following beneficial effects:

[0029] Compared to traditional dry coating methods that simply physically mix substances and coat them onto the surface of the substrate material, resulting in an uneven coating layer, the coating material in this application comprises at least one of aluminum oxides and / or hydroxides, aluminum-containing salts, and polyvinylidene fluoride (PVDF). This coating material can undergo a multi-step in-situ reaction with residual alkali on the substrate material surface to generate a uniform and stable coating layer. This reduces residual alkali while replenishing missing Na ions and forming strong bonds such as Na-O-Al, Na-F, TM-F, and Al-F, improving the stability of the outer layer structure. The AlF3 substance generated in the reaction has a significant promoting effect on cycle life and rate performance. The remaining PVDF is hydrophobic, and together with the coating layer, it prevents moisture and electrolyte from penetrating into the particles. In summary, the coating layer on the substrate material surface in this invention is not a simple physical coating, but rather obtained through an in-situ chemical reaction. The resulting coating layer has a good synergistic effect, reducing residual alkali on the surface of the sodium-ion battery cathode material and improving the cathode material's air stability, rate performance, and cycle stability. Attached Figure Description

[0030] Figure 1 This is a scanning electron microscope image of the sodium-ion battery cathode material in Example 5;

[0031] Figure 2 This is a scanning electron microscope image of the sodium-ion battery cathode material in Comparative Example 1;

[0032] Figure 3 Here is a scanning electron microscope image of the sodium-ion battery cathode material in Comparative Example 5;

[0033] Figure 4 Here is an HRTEM image of the sodium-ion battery cathode material in Example 5;

[0034] Figure 5 These are cycle comparison diagrams of the sodium-ion battery cathode materials in Examples 1-7 and Comparative Examples 1-7;

[0035] Figure 6 This is a rate comparison chart of sodium-ion battery cathode materials in Examples 1-7 and Comparative Examples 1-7. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0037] Example 1

[0038] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0039] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0040] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.2g and polyvinylidene fluoride of 0.2g;

[0041] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0042] Example 2

[0043] The main difference from Example 1 is that the aluminum oxide with an aluminum content of 0.2g in step S3 is replaced with aluminum hydroxide with an aluminum content of 0.2g.

[0044] Example 3

[0045] The main difference from Example 1 is that the aluminum oxide with an aluminum content of 0.2g in step S3 is replaced with aluminum oxide with an aluminum content of 0.1g and aluminum hydroxide with an aluminum content of 0.1g.

[0046] Example 4

[0047] The main difference from Example 1 is that step S3 is: take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating to obtain a secondary mixture, wherein the coating includes: aluminum oxide with an aluminum content of 0.6g, aluminum hydroxide with an aluminum content of 0.6g, and polyvinylidene fluoride of 1.2g.

[0048] Example 5

[0049] The main difference from Example 1 is that step S3 is: take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.4g and polyvinylidene fluoride of 0.4g.

[0050] Example 6

[0051] The main difference from Example 1 is that step S3 is: take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating to obtain a secondary mixture, wherein the coating includes: aluminum oxide with an aluminum content of 0.4g, aluminum hydroxide with an aluminum content of 0.4g, and polyvinylidene fluoride of 0.8g.

[0052] Example 7

[0053] S1. Sodium carbonate, nickel hydroxide, ferric oxide, manganese dioxide, titanium dioxide, and boron oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Ti:B = 1:0.332:0.331:0.328:0.004:0.005 to obtain a primary mixture.

[0054] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a sintering temperature of 1100℃ and a heating rate of 8℃ / min. After sintering for 8 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material NaNi. 0.332 Fe 0.33 1Mn 0.328 Ti 0.004 B 0.005 O2;

[0055] S3, Take 200g of matrix material NaNi 0.332 Fe 0.331 Mn 0.328 Ti 0.004 B 0.005 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.4g and polyvinylidene fluoride of 0.4g;

[0056] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 650℃ and a heating rate of 7℃ / min. After sintering for 5 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0057] Comparative Example 1

[0058] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a mixture.

[0059] S2. The mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the sodium-ion battery cathode material Na. 0.9 1Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2.

[0060] Comparative Example 2

[0061] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0062] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0063] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 and alumina with an aluminum content of 0.4g are mixed evenly to obtain a secondary mixture;

[0064] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0065] Comparative Example 3

[0066] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0067] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0068] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 and 0.4g of polyvinylidene fluoride are mixed evenly to obtain a secondary mixture;

[0069] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0070] Comparative Example 4

[0071] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0072] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0073] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.01g, aluminum hydroxide with an aluminum content of 0.01g, and polyvinylidene fluoride of 0.02g;

[0074] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0075] Comparative Example 5

[0076] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0077] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0078] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: aluminum oxide with an aluminum content of 2g, aluminum hydroxide with an aluminum content of 2g, and polyvinylidene fluoride with 2g.

[0079] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0080] Comparative Example 6

[0081] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0082] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0083] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.04g and polyvinylidene fluoride of 0.4g;

[0084] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0085] Comparative Example 7

[0086] S1. Sodium hydroxide, nickel oxide, ferric oxide, manganese tetroxide, magnesium oxide, and copper oxide are thoroughly mixed in a molar ratio of Na:Ni:Fe:Mn:Mg:Cu = 0.91:0.10:0.35:0.37:0.13:0.05 to obtain a primary mixture.

[0087] S2. The primary mixture was placed in an air atmosphere furnace for solid-state sintering at a temperature of 1000℃ and a heating rate of 5℃ / min. After sintering for 10 hours, it was cooled with the furnace, crushed in a dehumidifying room, and passed through a 300-mesh sieve to obtain the matrix material Na. 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2;

[0088] S3, Take 200g of matrix material Na 0.91 Ni 0.10 Fe 0.35 Mn 0.37 Mg 0.13. Cu 0.05 O2 is mixed evenly with the coating material to obtain a secondary mixture, wherein the coating material includes: alumina with an aluminum content of 0.4g and polyvinylidene fluoride of 0.04g;

[0089] S4. The secondary mixture is placed in an air atmosphere furnace for sintering at a temperature of 500℃ and a heating rate of 5℃ / min. After sintering for 6 hours, it is cooled with the furnace and then sieved under a dehumidified environment to obtain the coated sodium-ion battery cathode material.

[0090] The sodium-ion battery cathode materials of Examples 1-7 and Comparative Examples 1-7 were subjected to performance tests according to the following methods, and the test results are shown in the table below.

[0091] Table 1: Performance Test Data of Sodium-ion Battery Cathode Materials

[0092]

[0093] Comparing Examples 1-7 with Comparative Example 1, Table 1 shows that when the substrate material is coated with a coating material, the residual alkali on the surface of the sodium-ion battery cathode material can be effectively reduced, while the first discharge specific capacity, rate performance, cycle retention rate and air stability of the cathode material can be improved.

[0094] Comparing Examples 1-7 with Comparative Examples 2 and 3, Table 1 shows that, compared with using alumina or polyvinylidene fluoride alone as a coating material, the present invention mixes at least one of alumina and aluminum hydroxide with polyvinylidene fluoride as a coating material, which can effectively reduce the residual alkali on the surface of the cathode material of sodium-ion batteries, while improving the first discharge specific capacity, rate performance, cycle retention rate and air stability of the cathode material.

[0095] Comparing Examples 1-7 with Comparative Examples 4-7, Table 1 shows that both excessive and insufficient amounts of coating material, as well as excessive and insufficient amounts of each component in the coating material, will affect the electrochemical performance of the cathode material. At the same time, there is still a lot of residual alkali on the surface of the sodium-ion battery cathode material.

[0096] In summary, the present invention coats the substrate material with a coating of at least one of alumina and aluminum hydroxide and a mixture of polyvinylidene fluoride, which can effectively improve the initial discharge specific capacity, rate performance, cycle retention rate and air stability of the sodium-ion battery cathode material, and effectively reduce the residual alkali on the surface of the sodium-ion battery cathode material.

Claims

1. A coated sodium ion battery positive electrode material, characterized in that: It includes a base material and a coating layer covering the base material, wherein the coating layer is formed by a chemical reaction between the base material and the coating, and the chemical formula of the base material is Na n Ni a Fe b Mn c X d O2, wherein 0.8≤n≤2, 0.1≤a≤0.6, a+b+c≥0.7, d≤0.3, and X is selected from at least one of Ti, Mg, Zr, B, Al, Mo, Ca, Co, Li, Cu, Y, W, Sr, La, Nb, and Si; and the coating comprises: a mixture of at least one of aluminum oxide and / or hydroxide, and aluminum-containing salt and polyvinylidene fluoride.

2. A coated sodium ion battery positive electrode material according to claim 1, characterized in that: The total mass of aluminum element in the aluminum oxide and / or hydroxide and aluminum-containing salt is 1000-8000 ppm of the mass of the base material.

3. The coated sodium ion battery positive electrode material according to claim 1, characterized in that: The mass of the polyvinylidene fluoride is 1000-8000ppm of the mass of the base material.

4. The coated sodium ion battery positive electrode material according to claim 1, characterized in that: The coating includes a mixture of at least one of aluminum oxide and aluminum hydroxide and polyvinylidene fluoride.

5. The method for preparing the coated sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the sodium source, nickel source, iron source, manganese source and X source uniformly to obtain a primary mixture; S2, placing the primary mixture in an air atmosphere furnace for solid phase sintering, crushing, and sieving to obtain a matrix material; S3, mixing the base material and the coating material uniformly to obtain a secondary mixture; S4. The secondary mixture is placed in an air atmosphere furnace for sintering and sifted to obtain a coated sodium ion battery positive electrode material.

6. The preparation method according to claim 5, characterized in that: In the step S1, the sodium source is selected from at least one of sodium hydroxide and salts containing sodium, the nickel source is selected from at least one of nickel oxides, hydroxides and salts containing nickel, the iron source is selected from at least one of iron oxides, hydroxides and salts containing iron, the manganese source is selected from at least one of manganese oxides, hydroxides and salts containing manganese, and the X source is selected from at least one of X oxides, hydroxides and salts containing X.

7. The preparation method according to claim 5, characterized in that: In the step S2, the sintering temperature is 900-1100° C., and the sintering time is 8-12 hours.

8. The preparation method according to claim 5, characterized in that: In the step S2, the mesh size of the sieve is 200 to 400 meshes.

9. The preparation method according to claim 5, characterized in that: In the step S4, the sintering temperature is 250-650° C., and the sintering time is 4-8 hours.

10. A sodium ion battery, characterized in that: The positive electrode of the sodium ion battery comprises the coated sodium ion battery positive electrode material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Hydrophobic polymer coated modified sodium battery positive electrode material, preparation method and battery

    CN115954447A

Cited By

  • Composite positive electrode material and preparation method and application thereof

    CN120319790A